Impact of the gut microbiota on immune checkpoint inhibitor-associated toxicities. (September 2019) - Pezo, Rossanna C.; Wong, Matthew; Martin, Alberto
Immune checkpoint inhibitors (ICIs) have transformed the treatment of patients with advanced cancers. However, the majority of patients do not respond or develop early progressive disease. A substantial number also develop immune-mediated toxicities that may lead to early treatment discontinuation. Gastrointestinal toxicities in the form of diarrhea and colitis are common and may resemble that observed in patients with inflammatory bowel disease (IBD). Alterations in the gut microbiota are thought to play an important role in mediating the intestinal inflammation that is associated with immune-mediated colitis. In this review, the authors' objective is to provide an overview of the gastrointestinal and hepatic toxicities that can be seen with ICIs and discuss the interactions between gut microbiota and the immune response. The authors also highlight the potential role for fecal microbial transfer (FMT) as an approach to improve therapeutic efficacy and decrease toxicity.